2009
DOI: 10.1002/cm.20349
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin‐5 in Drosophila embryo mitosis: Sliding filament or spindle matrix mechanism?

Abstract: The Drosophila syncytial embryo uses multiple astral mitotic spindles that are specialized for rapid mitosis. The homotetrameric kinesin‐5, KLP61F contributes to various aspects of mitosis in this system, all of which are consistent with it exerting outward forces on spindle poles. In principle, kinesin‐5 could accomplish this by (i) sliding microtubules (MTs), minus end leading, relative to a static spindle matrix or (ii) crosslinking and sliding apart adjacent pairs of antiparallel interpolar (ip) MTs. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 55 publications
2
20
0
Order By: Relevance
“…Recent studies have resolved key aspects of the structure and functionality of kinesin-12 (Drechsler et al, 2014;Klejnot et al, 2014), with the idea that interfering with kinesin-12 function could be exploited for cancer therapy. In previous studies, kinesin-12 was found to promote bipolar spindle formation by cooperating with kinesin-5 (also called Eg5 or Kif11), a tetrameric motor protein important for cell division (Kashina et al, 1996;Scholey, 2009;Ferenz et al, 2010). These studies revealed that kinesin-12 is not required for spindle bipolarity in cells with full Eg5 activity but becomes essential when Eg5 is partially inhibited (Tanenbaum et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have resolved key aspects of the structure and functionality of kinesin-12 (Drechsler et al, 2014;Klejnot et al, 2014), with the idea that interfering with kinesin-12 function could be exploited for cancer therapy. In previous studies, kinesin-12 was found to promote bipolar spindle formation by cooperating with kinesin-5 (also called Eg5 or Kif11), a tetrameric motor protein important for cell division (Kashina et al, 1996;Scholey, 2009;Ferenz et al, 2010). These studies revealed that kinesin-12 is not required for spindle bipolarity in cells with full Eg5 activity but becomes essential when Eg5 is partially inhibited (Tanenbaum et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Microtubules and actin play a key role in maintaining an ordered pattern and in driving motion (12). Possible force generators during interphase are Kinesin-5 motors between overlapping microtubules, direct active interactions of astral microtubules with nuclei, or active interaction of microtubules with the actin caps via dyneindynactin complexes (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the movement might be caused by a dedicated mechanism, and possibly be motor-driven, much like microtubule-microtubule sliding in the mitotic spindle. Microtubule sliding by the plus-end-directed kinesin motor Klp61F (7,8), the minus-end-directed kinesin Ncd (9), and the minus-end-directed cytoplasmic dynein motor (9) are required for proper spindle separation during anaphase. However, Klp61F and Ncd activity is limited to mitosis (10,11).…”
mentioning
confidence: 99%